A study of ZnO:Al thin films reactively sputtered under the control of target voltage for application in Cu(In, Ga)Se2 thin film solar cells. (March 2019) - Zhu, H.; Niu, X.; Wan, M.; Mai, Y.
Abstract: In this study, aluminum doped zinc oxide (ZnO:Al) thin films were prepared by reactive magnetron sputtering from Zn:Al metallic targets with different Al contents (0.5 wt%, 1.5 wt%, 2.0 wt% and 2.5 wt%). The reactive sputtering process was monitored and controlled with a gas loop controller. The crystal structures, morphologies, chemical compositions, optical and electrical properties of the reactively sputtered ZnO:Al thin films were systematically investigated. In addition, the reactively sputtered ZnO:Al thin films were applied as window layers in Cu(In, Ga)Se2 (CIGS) thin film solar cells. The corresponding performances of solar cells were also studied. High efficiency of 16.2% was achieved for CIGS thin film solar cells with reactively sputtered ZnO:Al window layers in this study, which was slightly lower than 17% of reference cell with radio frequency (RF) non-reactively sputtered ZnO:Al window layer. Highlights: ZnO:Al thin films were prepared by DC reactive sputtering from Zn:Al metallic targets. The reactive sputtering process were monitored and controlled with a gas loop controller. DC sputtered ZnO:Al thin films were applied as window layers in CIGS thin film solar cells.